Dynamic Analysis and Isolation Effectiveness of a Low Stiffness Nonlinear Isolator - Nguyen , Minh Ky; Le, Thanh Danh; Vo, Ngoc Yen Phuong (Journal of Technical Education Science, 2022)
This paper presents a low stiffness nonlinear vibration isolator using a pneumatic spring with an auxiliary chamber which is shortened by LSNVI. Firstly, the mechanical model of the isolator, which is constructed by two opposite stiffness mechanisms includes the load bearing mechanism (LBM) and the stiffness corrected mechanism (SCM), is introduced. Secondly, the restoring force of the model is found. Based on this, the dynamic stiffness is calculated numerically. Then, the spring force curve was approximated by expanding the Taylor series to order-5. Next, a numerical simulation is carried out to investigate the effect of the pressure ratio on the system stiffness. Simultaneously, by using the Multi-scale method, the frequency-amplitude relation curve is analyzed. The vibration transmissibility characteristic of the LSNVI is simulated and compared with that of the equivalent traditional nonlinear vibration isolator (named NVI-non SCM) in which the SCM is removed. The simulation results illustrate that the isolation effectiveness of the former is better than the latter. This result shows that the LSNVI can offer a vision isolation performance. This presentation furnishes a useful insight into the design for low frequency vibration isolation model